Isolation and Characterization of the Expression of Gene for Sucrose Transporter Proteins in Sugarcane Plant (Saccharum officinarum) - Harianti Novita; Tri Agus Siswoyo; Bambang Sugiharto (Jurnal ILMU DASAR, 2007)
Sucrose as the major transported form of fixed carbon must be translocated from source tissue to the sites of consumption and storage or sink tissues. The translocation of sucrose is facilitated by some distinct sucrose transporters proteins (SUT). To study sucrose transporters in sugarcane, we had conducted isolation and characterization of gene encoding sucrose transporter protein. The isolation was performed with RT-PCR method using total RNA isolated from sugarcane leaf and primer designed from conservative region of SUTcDNAs of SoSUT2A (accession number AY65599), OsSUT-1(accession number AAP54842, OsSUT-1 mRNA (accession number XM 46477). Based on the conservative amino acids sequences of QILQQFA and MGKTEPV, the corresponding sequences of the primers for RT-PCR were: P1, (forward) 5’CAGATCCTTCAACAGTTCGC-3’ and P2 (reverse) 5’-TGCCCTTTGTCTCCGGAACC-3’, respectively. Agarose gel electrophoresis shown a clear single 0.5 kb cDNA band of the PCR product. Thus, the DNA was cloned into pGEMT vector (Promega) for further analysis. Sequence determination of the PCR product revealed a nucleotides sequence of 543 bp in length and has a high homology around 89%, 87.3 % and 84.8 % with maize ZmSUT-1, sugarcane SoSUT 2A and rice OsSUT-1 mRNA, respectively. We designated the cDNA as SoSUT2 and the nucleotide sequence have been submitted to GenBank data base under accession number bankit 734628. By using PSORT analysis the fragment of cDNA-SoSUT2 encoded protein may be located in the endoplasmic reticulum. To have a better understanding, the expression of SoSUT2 gene in sugarcane was determinate by RT-PCR method using total RNA isolated from leaf, petioles, stem and root and visualized the PCR product in agarose gel electrophoresis. Based on the cDNA bands intensity, it can be illustrated that the expression of SoSUT2 gene were found highest in sugarcane leafs then petioles and stem, but the expression was not found in root. Although the SoSUT2-cDNA has not been isolated in full size, the results suggest the presence of gene family of SUT in sugarcane.